2021
DOI: 10.1016/j.ensci.2021.100324
|View full text |Cite
|
Sign up to set email alerts
|

Detect it so you can treat it: A case series and proposed checklist to detect neurotoxicity in checkpoint therapy

Abstract: Background Checkpoint inhibitors show impressive and durable responses in various cancer types and provide new avenues for cancer immunotherapy. However, these drugs have a variety of adverse events. Common autoimmune-related adverse effects include fatigue, hepatitis, skin rash, endocrine deficiencies, and colitis. Neurotoxicity has been reported, but its incidence and course remain unclear. Methods To illustrate the broad spectrum of neurotoxicity, we exemplarily repo… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 40 publications
0
9
0
Order By: Relevance
“…ICI-related neurological adverse events are relatively infrequent; however, pooled analyses have shown that they are associated with increased morbidity and mortality ( 3 5 ). Myasthenia gravis (MG) is an autoimmune disorder mediated by autoantibodies, including anti-acetylcholine receptor (AChR) or anti-muscle associated receptor tyrosine kinase (MUSK) antibodies that target the neuromuscular junction ( 6 ).…”
Section: Introductionmentioning
confidence: 99%
“…ICI-related neurological adverse events are relatively infrequent; however, pooled analyses have shown that they are associated with increased morbidity and mortality ( 3 5 ). Myasthenia gravis (MG) is an autoimmune disorder mediated by autoantibodies, including anti-acetylcholine receptor (AChR) or anti-muscle associated receptor tyrosine kinase (MUSK) antibodies that target the neuromuscular junction ( 6 ).…”
Section: Introductionmentioning
confidence: 99%
“…Myositis due to irAEs has also been reported, especially myocarditis, which is known to have a high fatality rate [ 14 ]. In addition, some reports have described Guillain-Barre syndrome or myasthenia gravis developing as an irAE due to ICIs, and these diagnoses need to be ruled out when symptoms of muscle weakness are present [ 15 ]. In the present case, muscle cramps and grasping pain were observed, but no symptoms such as muscle weakness, decreased swallowing function, or dyspnea were apparent, so Guillain-Barre syndrome and myasthenia gravis were not suspected.…”
Section: Discussionmentioning
confidence: 99%
“…The resulting nerve damage causes varying degrees of weakness, sensory loss, and autonomic dysfunction. Checkpoint inhibitors have been associated with acute transverse myelitis in case reports and series [ 73 , 107 , 117 , [124] , [125] , [126] , [127] , [128] , [129] ].…”
Section: Demyelination: Acute Transverse Myelitismentioning
confidence: 99%
“…Almost all patients present with rapidly progressive lower extremity paraparesis, sensory loss and sphincter dysfunction [ 130 ]. There are reports of tetraparesis [ 126 , 128 ]. Deep tendon reflexes may be affected, and Babinski sign may be present [ 124 ].…”
Section: Demyelination: Acute Transverse Myelitismentioning
confidence: 99%